Temporally Dissociated, Trait-Specific Modifications Underlie Phenotypic Polyphenism in Spea multiplicata Tadpoles, Which Suggests Modularity - Brian L. Storz; Joseph Travis (The Scientific World Journal)
Many organisms that develop in a variable environment show correlated patterns of phenotypic plasticity in several traits. Any individual trait modification can be beneficial, neutral, or deleterious in any particular environment; the organism's total fitness, which determines if the plasticity is adaptive, is the sum of these changes. Although much is known about how plastic traits contribute to fitness, less is known about the extent to which the various trait changes involved in the plastic responses share their developmental control. Shared control suggests that the various responses evolved in unison, but independent control suggests independent evolution of many components. Spadefoot toads have evolved adaptive polyphenism to cope with developing in rapidly drying ephemeral ponds. Larvae hatch as omnivores, but on exposure to an environmental cue, may develop into carnivores. We compared trait development in the two morphs and found that differences in jaw musculature, head dimensions, and intestines emerged early in development, whereas differences in shape of the tail emerged later. In omnivores, all traits except intestine length and hind-limb length were negatively allometric with body length; in carnivores, two of three jaw muscles displayed positive allometry and, among those that were negatively allometric, all except head width showed larger allometric coefficients in carnivores. Hind-limb length was positively allometric in both forms, but the allometric coefficients did not differ significantly. Intestine length was positively allometric to body length in both forms, but in this case, omnivores exhibited the higher coefficient. These results suggest that spadefoot plasticity is trait specific and the responses are suggestive of the existence of at least two modules: a suite of trophic traits that responds early in development and a suite of tail traits that responds later. The developmental control of these suites is the subject of further investigation.